Nanometer zirconia ceramic material for dental restoration and preparation method thereof
Through the method of preparing nanozirconia ceramic materials, the problems of complex preparation processes, high cost and insufficient performance of existing materials are solved, and the efficient preparation and excellent performance of the materials are achieved, which is suitable for dental restoration.
Patent Information
- Application Number
- CN202411696353.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
In dental restoration, existing nanozirconia ceramic materials have problems such as complex preparation process, high cost, micro leakage, and insufficient mechanical properties, biocompatibility, chemical stability and antibacterial properties.
A preparation method is adopted, including the preparation of nanozirconia powder, composite spherical powder and blanks, and through molding, thermal isostatic pressing and multi-stage heating and sintering, nanozirconia ceramic materials with excellent mechanical properties, biocompatibility, chemical stability and antibacterial properties are formed.
It realizes efficient preparation of materials, has high bending strength, high fracture toughness, good biocompatibility and antibacterial properties, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure BDA0005152182830000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dental restoration materials, and in particular to a nano-zirconia ceramic material for dental restoration and a preparation method thereof. Background Art
[0002] Zirconia ceramics have been widely used in the field of dental restorations due to their high strength, good biocompatibility and superior aesthetic effects. At present, there are many zirconia ceramic products on the market, such as Prettau Zirconia, Bruxzir Zirconia BRX, Wieland Zenostar Translucent ZEN, etc. These products are mainly used to make all-zirconia crowns and bridges, all-ceramic bottom crowns, and three-unit or four-unit bridges for anterior and posterior teeth. At present, the preparation process of nano-zirconia ceramic materials is relatively complicated, and it is necessary to accurately control parameters such as raw material ratio, sintering temperature and time to ensure the performance and quality of the materials. Due to the complex preparation process and high raw material cost, the cost of nano-zirconia ceramic materials is relatively high, which limits its wide application in dental restorations. When nano-zirconia ceramic materials are used as restorations such as posts and cores, there may be problems of microleakage, and their mechanical properties, biocompatibility, chemical stability and antibacterial properties need to be improved. Summary of the invention
[0003] In view of the above defects or improvement needs of the prior art, the present application provides a nano-zirconia ceramic material for dental restoration and a preparation method thereof. The nano-zirconia ceramic material for dental restoration prepared in the present application has excellent mechanical properties (high bending strength, high fracture toughness), biocompatibility, chemical stability and antibacterial properties. At the same time, the preparation method of the present application has a simple process and low cost, and can be effectively applied to mass production. In addition, the nano-zirconia powder prepared in the present application has a large specific surface area, a small particle size and a uniform particle size distribution, stable tetragonal phase crystals and excellent antibacterial properties.
[0004] In a first aspect, the present application provides a method for preparing a nano-zirconia ceramic material for dental restoration, using the following technical solution: A method for preparing a nano-zirconia ceramic material for dental restoration comprises the following steps: S1, preparing nano zirconium oxide powder; S2. Preparation of composite spherical powder: The composite spherical powder includes the following raw materials by mass: 100 parts of nano zirconium oxide powder, 3 parts of barium glass powder, 3.5 parts of binder, 1 part of dispersant, 10 parts of ethanol, and 140 parts of deionized water; S3, preparing a green body: molding the composite spherical powder under a pressure of 10 MPa to obtain a molded green body with a volume of V, and vacuum packaging the green body; placing the packaged green body into a 170° C. hot isostatic press, pressurizing it to 200 MPa, maintaining the pressure for 20 minutes, and then releasing the pressure to obtain a hot pressed green body with a volume of 83% V; S4. High temperature sintering: After the hot pressed green body is unpacked and subjected to high temperature sintering, the nano-zirconia ceramic material for dental restoration is obtained.
[0005] By adopting the above technical scheme, the preparation of nano zirconium oxide powder: the soluble zirconium salt and yttrium salt are embedded and modified by carboxymethyl cellulose, and the synergistic effect of surfactant and propylene glycol makes the zirconium salt, yttrium salt and silver salt uniformly dispersed during the precipitation process, and the final zirconium oxide particles are smaller and evenly distributed. This modification method not only improves the strength and toughness of the material, but also enhances its antibacterial properties and biocompatibility. Preparation of composite spherical powder: by adding barium glass powder, introducing a composite reinforcement phase, and infiltrating molten barium glass on the microporous scaffold constructed by zirconium oxide, the translucency and mechanical properties of the material can be significantly improved. This preparation method of composite spherical powder helps to improve the overall performance of the material. Preparation of green body: by molding the composite spherical powder under a pressure of 10MPa, then vacuum packaging the green body, and pressurizing it to 200MPa in a hot isostatic press at 170℃, and releasing the pressure after maintaining the pressure for 20min, this method can significantly reduce the occurrence of processing defects such as collapse, cracks, and holes during high-temperature sintering. High temperature sintering: Through multi-stage heating sintering and cooling and tempering treatment, processing defects such as chipping, cracks, and holes generated during the sintering process can be further reduced. At the same time, cooling and tempering treatment can ensure the balance between the strength and toughness of nano-zirconia ceramic materials, and improve their quality and service life. In general, this application achieves efficient preparation of nano-zirconia ceramic materials by precisely controlling the process parameters and operating conditions of each step. The synergistic effect between the steps makes the final prepared material have excellent mechanical properties, biocompatibility, chemical stability and antibacterial properties, while maintaining the simplicity and low cost of the process, which is suitable for mass production.
[0006] Preferably, in step S1, the method for preparing the nano zirconium oxide powder comprises the following steps: S21, adding a soluble zirconium salt, a soluble yttrium salt, silver nitrate, a surfactant, glycerol, and carboxymethyl cellulose into deionized water, and dissolving them to form a solution A; S22, adding solution A dropwise to an alkaline precipitant to carry out precipitation reaction for 40 minutes, then adding oleic acid and stirring for reaction for 30 minutes to obtain a suspension; S23, aging the suspension at 35° C. for 24 hours, filtering, washing with water and washing with alcohol to obtain a hydrated zirconium gel; S24. The hydrated zirconium gel was heated for 20 minutes under a microwave condition with a power of 500 W for drying, and then calcined at 480° C. in an air atmosphere for 2.5 hours to obtain nano zirconium oxide powder.
[0007] By adopting the above technical scheme, S21, soluble zirconium salt, silver nitrate soluble yttrium salt, surfactant, glycerol, and carboxymethyl cellulose are added to deionized water, dissolved, and solution A is formed; this step is to mix various raw materials together to form a uniform solution. Among them, soluble zirconium salt and soluble yttrium salt are the main raw materials, which will generate zirconium oxide and yttrium oxide in the subsequent precipitation reaction. The addition of silver nitrate is to enhance the antibacterial properties of nano zirconium oxide powder. The role of surfactant is to increase the electrostatic repulsion of Zr4+ in the solution to prevent it from agglomerating during the precipitation process. The addition of glycerol can cooperate with surfactants through its hydroxyl hydrophilic effect to make zirconium salt, yttrium salt, and silver salt uniformly dispersed during the precipitation process. Carboxymethyl cellulose, as a water-soluble polymer, can achieve the embedding modification of soluble zirconium salt and soluble yttrium salt to avoid their agglomeration during the precipitation process. S22. Add solution A dropwise to the alkaline precipitant for precipitation reaction for 40 minutes, then add oleic acid and stir for reaction for 30 minutes to obtain a suspension; this step is to convert the zirconium salt and yttrium salt in the solution into hydroxide form through precipitation reaction to form a suspension. The addition of oleic acid can further improve the dispersibility of the particles. S23. After aging the suspension at 35°C for 24 hours, filter, wash with water and wash with alcohol to obtain a hydrated zirconium gel; this step is to age the suspension to further grow and stabilize the particles. Then remove impurities and solvents by filtering, washing with water and washing with alcohol to obtain a pure hydrated zirconium gel. S24. Heat the hydrated zirconium gel under a microwave condition of 500W power for 20 minutes for drying, and calcine it at 480°C in an air atmosphere for 2.5 hours to obtain nano zirconium oxide powder. This step is to convert the hydrated zirconium gel into nano zirconium oxide powder by microwave drying and high-temperature calcination. In this process, the presence of carboxymethyl cellulose can prevent the agglomeration of particles during calcination, keeping the particle size small and uniformly distributed. At the same time, in-situ doping of yttrium oxide and silver ions can improve the strength, toughness and antibacterial properties of the material.
[0008] Preferably, in step S21, the soluble zirconium salt is zirconium oxychloride octahydrate; the soluble yttrium salt is yttrium acetate; Preferably, the surfactant is composed of coconut oil fatty acid diethanolamine and lauryl alcohol polyoxyethylene ether in a mass ratio of 1:2.
[0009] Preferably, in step S21, the mass ratio of the soluble zirconium salt, the soluble yttrium salt, silver nitrate, the surfactant, glycerol, carboxymethyl cellulose and deionized water is 322:45:9:65:20:13:500.
[0010] Preferably, in step S22, the alkaline precipitant is prepared by mixing ammonium carbonate and 25% ammonia water in a mass ratio of 5:7.
[0011] Preferably, in step S22, the mass ratio of oleic acid to solution A is 1:80-90.
[0012] Preferably, in step S2, the binder is composed of polyvinyl alcohol and hydroxycellulose in a mass ratio of 1:1; and the dispersant is ammonium citrate.
[0013] Preferably, in step S2, the preparation method of the composite spherical powder is: according to the mass fraction, nano zirconium oxide powder and barium glass powder are placed in a polyurethane-lined ball mill, and zirconium oxide beads 3 times the mass of the nano zirconium oxide powder are added at the same time, and then deionized water, ethanol and dispersant are added in sequence, at a speed of 50 rpm; after ball milling for 0.6 h, a binder is added and ball milling is continued for 1.2 h; the slurry is filtered to obtain a slurry, and the slurry is spray granulated, and during granulation, the feed inlet temperature is 260°C, the discharge port temperature is 115°C, the atomization frequency is 170 Hz, and the blowing pressure is 0.6 MPa to obtain a composite spherical powder.
[0014] By adopting the above technical scheme, raw material mixing: nano zirconium oxide powder and barium glass powder are mixed in proportion and put into a ball mill jar, and zirconium oxide beads are added. The mass of zirconium oxide beads is three times that of nano zirconium oxide powder, which helps to improve the ball milling efficiency and make the powder more evenly mixed and refined. Preliminary ball milling: after adding deionized water, ethanol and dispersant, ball milling is carried out at a speed of 50rpm for 0.6 hours. The purpose of this step is to preliminarily mix and refine the powder to ensure that the components are evenly distributed. Adding binder: after ball milling for 0.6 hours, add binder and continue ball milling for 1.2 hours. The addition of binder helps to improve the molding properties of the powder, making it easier to form a uniform tung body in the subsequent compression molding process. Spray granulation: the ball-milled slurry is spray granulated. The feed inlet temperature during granulation is 260℃℃, the outlet temperature is 115℃℃, the atomization frequency is 170Hz, and the blowing pressure is 0.6MPa. These parameters ensure that the slurry can form uniform spherical particles during the spraying process. Through spray granulation, composite spherical powder with uniform particle size and good fluidity can be obtained. This powder can be packed more tightly in the subsequent compression molding process, reduce porosity, and improve the density and uniformity of the green body. Synergistic effect of nano zirconium oxide powder and barium glass powder The addition of barium glass powder not only improves the translucency of the material, but also forms a composite material with zirconium oxide during high-temperature sintering to enhance the mechanical properties of the material. The infiltration of molten barium glass on the microporous support constructed by zirconium oxide significantly improves the translucency and mechanical properties of the material. The ball milling process ensures uniform mixing and refinement of the powder, while spray granulation converts these refined powders into spherical particles with good fluidity and uniform particle size. These two steps complement each other and jointly improve the performance of the final product. The addition of a binder improves the molding properties of the powder, making it easier to form a uniform and dense green body during compression molding. This is crucial for the subsequent hot isostatic pressing and high-temperature sintering processes, as these processes require the green body to have a high density and uniformity. In short, the composite spherical powder prepared by the precisely controlled ball milling and spray granulation process has good fluidity and uniform particle size distribution, which lays a solid foundation for subsequent compression molding and high-temperature sintering. This composite spherical powder not only improves the mechanical properties and translucency of the material, but also simplifies the production process, reduces costs, and is suitable for mass production. Preferably, in step S4, the process conditions of the high-temperature sintering are: heating to 550°C at a rate of 1°C / min, keeping warm for 3h, then heating to 900-1000°C at 2°C / min and keeping warm for 2h, then heating to 1400-1450°C at 3°C / min and keeping warm for 1h, then cooling to 500°C at a rate of 2°C / min, keeping warm for 5h for tempering, and finally cooling to room temperature at a rate of 20°C / min.
[0015] By adopting the above technical scheme, low temperature section (heating to 550℃ at a rate of 1℃ / min): At this stage, the temperature is relatively low, and the main purpose is to remove moisture and organic matter in the blank to avoid cracking or deformation of the blank caused by rapid heating. Keep warm for 3 hours to ensure that moisture and organic matter are fully volatilized. Medium temperature section (heating to 900-1000℃ at 2℃ / min): The temperature at this stage is moderate, which helps to further remove residual organic matter and start the initial crystallization of zirconium oxide. Keep warm for 2 hours to stabilize the growth of grains and prevent excessive grain growth. At high temperature section (heating to 1400-1450℃ at 3℃ / min), the grains of zirconium oxide will further grow and improve at high temperature to form a more compact and uniform structure. Keep warm for 1 hour to ensure full growth of grains and improve the density and mechanical properties of the material. Cooling and tempering treatment: Slow cooling can reduce thermal stress and prevent cracks or deformation of the material during cooling. Tempering treatment is to eliminate residual stress inside the material and improve the toughness and stability of the material. Keeping the material warm for 5 hours can ensure that the internal stress of the material is fully released. Rapid cooling After tempering, the material is relatively stable. Timing can quickly cool to room temperature to improve production efficiency. Through multi-stage heating and sintering, processing defects such as collapse, cracks and holes caused by rapid heating can be avoided, and the density and uniformity of the material can be improved. The balance between strength and toughness can be achieved through precise heating and cooling rate control, as well as tempering treatment, while ensuring the high strength of the material, while improving its toughness, making the material more durable in practical applications. The design of the entire high-temperature sintering process is to optimize the microstructure of zirconia ceramics, so that it has excellent mechanical properties and biocompatibility, thereby improving the quality and service life of the material. In short, through the precisely controlled high-temperature sintering process, the nano-zirconia ceramic material for dental restoration in this application can have good biocompatibility and chemical stability while maintaining high bending strength and high fracture toughness. In addition, the process also gives the material excellent antibacterial properties, making it perform well in clinical applications. This comprehensive performance improvement makes the material very suitable for use in the field of high-performance dental restoration.
[0016] In the second aspect, the present application provides a nano-zirconia ceramic material for dental restoration, which adopts the following technical solution: As a general technical concept, the present application also provides the above-mentioned nano-zirconia ceramic material for dental restoration, which is prepared by the above-mentioned preparation method of the nano-zirconia ceramic material for dental restoration.
[0017] In summary, the beneficial technical effects of this application are: 1. Excellent mechanical properties: high bending strength and high fracture toughness, including uniform dispersion of nano zirconium oxide powder through precisely controlled preparation process, preparation of composite spherical powder, hot isostatic pressing treatment and multi-stage temperature sintering, so that the final nano zirconium oxide ceramic material has extremely high bending strength and fracture toughness. These excellent mechanical properties make the material perform well when subjected to chewing force and other mechanical stresses, reducing the risk of damage to the restoration during use.
[0018] 2. Biocompatibility and chemical stability Good biocompatibility: By adding silver ions and yttrium salts, not only the antibacterial properties of the material are improved, but also its biocompatibility is enhanced, making it more suitable for dental restoration. This material is well compatible with human tissues and reduces the occurrence of inflammatory reactions and other adverse reactions.
[0019] Chemical stability: Nano-zirconia ceramic materials show good chemical stability in the oral environment, can resist acid and alkali corrosion and other chemical changes, and extend the service life of the restoration.
[0020] 3. Excellent antibacterial properties: The antibacterial properties of the material are significantly improved by in-situ doping with silver ions. This is of great significance for preventing oral infection and inflammation, especially in long-term dental restorations, which can effectively reduce bacterial growth and maintain oral health.
[0021] 4. Translucency and aesthetics: Improving translucency Adding barium glass powder and using hot isostatic pressing significantly improves the translucency of the material. This makes the restoration look closer to natural teeth and meets the patient's aesthetic needs.
[0022] 5. Simple process, low cost, suitable for mass production: The entire preparation process includes the preparation of nano zirconium oxide powder, the preparation of composite spherical powder, the molding of the green body and high-temperature sintering. The process is relatively simple and easy to operate. Due to the use of low-cost raw materials and simple process equipment, the overall production cost is low, which is conducive to large-scale production and application. The preparation method is reasonably designed and highly repeatable, suitable for industrial mass production, and can meet the market demand for high-quality dental restoration materials.
[0023] 6. Reduce processing defects and improve yield: By precisely controlling the hot isostatic pressing process parameters and multi-stage temperature rise sintering, the occurrence of processing defects such as chipping, cracks, and holes during high-temperature sintering is significantly reduced, and the yield and material quality are improved.
[0024] 7. Improve the comprehensive performance of materials: Through a variety of modification methods and optimization processes, the mechanical properties, biocompatibility, antibacterial properties and aesthetics of nano-zirconia ceramic materials have been comprehensively improved, making it an ideal dental restoration material. DETAILED DESCRIPTION
[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0026] In the following examples and preparation examples, 1 part means 100 g.
[0027] Preparation Example 1 Preparation of Nano Zirconia Powder The preparation method of nano zirconium oxide powder comprises the following steps: S21, 322g zirconium oxychloride octahydrate, 45g yttrium acetate, 9g silver nitrate, 65g surfactant (composed of coconut oil fatty acyl diethanolamine and lauryl alcohol polyoxyethylene ether in a mass ratio of 1:2), 20g glycerol, and 13g carboxymethyl cellulose were added to 500g deionized water and dissolved to form solution A; S22, taking 70g of ammonium carbonate and adding 70g of 25wt% ammonia water and mixing them evenly to obtain a mixed alkaline solution (i.e., alkaline precipitant), then adding solution A dropwise to the alkaline precipitant to carry out precipitation reaction for 40 minutes, then adding 11g of oleic acid and stirring the reaction for 30 minutes to obtain a suspension; S23, aging the suspension at 35° C. for 24 hours, filtering, washing with water and washing with alcohol to obtain a hydrated zirconium gel; S24. The hydrated zirconium gel was heated for 20 minutes under a microwave condition with a power of 500 W for drying, and then calcined at 480° C. in an air atmosphere for 2.5 hours to obtain nano zirconium oxide powder.
[0028] The diameter of the nano-zirconia powder prepared above was tested by a laser particle size analyzer (DLS), and the specific surface area was tested by a pore size and specific surface area analyzer (BET). The test results showed that the D10 of the nano-zirconia powder was 4.05 nanometers, the D50 of the nano-zirconia powder was 10.25 nanometers, the D90 of the nano-zirconia powder was 18.50 nanometers, and the specific surface area was 185.35 m 2 / g.
[0029] Preparation Example 2 Preparation of composite spherical powder The composite spherical powder includes the following raw materials by weight: 100 parts of nano zirconium oxide powder, 3 parts of barium glass powder, 3.5 parts of binder, 1 part of dispersant, 10 parts of ethanol, and 140 parts of deionized water; the binder is composed of polyvinyl alcohol and hydroxy cellulose in a weight ratio of 1:1; the dispersant is ammonium citrate; the nano zirconium oxide powder is prepared by Preparation Example 1.
[0030] The preparation method of the composite spherical powder is as follows: according to the mass fraction, nano zirconium oxide powder and barium glass powder are put into a polyurethane-lined ball mill, and zirconium oxide beads with a mass three times that of the nano zirconium oxide powder are added at the same time, and then deionized water, ethanol and a dispersant are added in sequence, and the speed is 50 rpm; after ball milling for 0.6 hours, a binder is added and the ball milling is continued for 1.2 hours; the slurry is filtered to obtain the slurry, and the slurry is sprayed and granulated, and during the granulation, the feed inlet temperature is 260° C., the discharge port temperature is 115° C., the atomization frequency is 170 Hz, and the blowing pressure is 0.6 MPa to obtain the composite spherical powder.
[0031] Preparation of Comparative Example 1 Preparation of composite spherical powder The same as Preparation Example 2, except that the nano zirconium oxide powder is yttrium-stabilized zirconium oxide from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd., CAS: 114168-16-0.
[0032] Example 1 A method for preparing a nano-zirconia ceramic material for dental restoration comprises the following steps: S1. Preparing a green body: molding the composite spherical powder (composite spherical powder prepared in Preparation Example 2) under a pressure of 10 MPa to obtain a molded green body with a volume of V, and vacuum packaging the green body; placing the packaged green body in a 170° C. hot isostatic press, pressurizing it to 200 MPa, maintaining the pressure for 20 min, and then releasing the pressure to obtain a hot pressed green body with a volume of 83% V; S2. High-temperature sintering: After the hot-pressed green body is unpacked and subjected to high-temperature sintering, a nano-zirconia ceramic material for dental restoration is obtained, wherein the process conditions for the high-temperature sintering are: heating to 550°C at a rate of 1°C / min, keeping warm for 3 hours, then heating to 900°C at a rate of 2°C / min and keeping warm for 2 hours, then heating to 1450°C at a rate of 3°C / min and keeping warm for 1 hour, then cooling to 500°C at a rate of 2°C / min, keeping warm for 5 hours for tempering, and finally cooling to room temperature at a rate of 20°C / min.
[0033] Example 2 A method for preparing a nano-zirconia ceramic material for dental restoration comprises the following steps: S1. Preparing a green body: molding the composite spherical powder (composite spherical powder prepared in Preparation Example 2) under a pressure of 10 MPa to obtain a molded green body with a volume of V, and vacuum packaging the green body; placing the packaged green body in a 170° C. hot isostatic press, pressurizing it to 200 MPa, maintaining the pressure for 20 min, and then releasing the pressure to obtain a hot pressed green body with a volume of 83% V; S2. High-temperature sintering: After the hot-pressed green body is unpacked and subjected to high-temperature sintering, a nano-zirconia ceramic material for dental restoration is obtained, wherein the process conditions for the high-temperature sintering are: heating to 550°C at a rate of 1°C / min, keeping warm for 3 hours, then heating to 1000°C at a rate of 2°C / min and keeping warm for 2 hours, then heating to 1400°C at a rate of 3°C / min and keeping warm for 1 hour, then cooling to 500°C at a rate of 2°C / min, keeping warm for 5 hours for tempering, and finally cooling to room temperature at a rate of 20°C / min.
[0034] Example 3 A method for preparing a nano-zirconia ceramic material for dental restoration comprises the following steps: S1. Preparing a green body: molding the composite spherical powder (composite spherical powder prepared in Preparation Example 2) under a pressure of 10 MPa to obtain a molded green body with a volume of V, and vacuum packaging the green body; placing the packaged green body in a 170° C. hot isostatic press, pressurizing it to 200 MPa, maintaining the pressure for 20 min, and then releasing the pressure to obtain a hot pressed green body with a volume of 83% V; S2. High-temperature sintering: After the hot-pressed green body is unpacked and subjected to high-temperature sintering, a nano-zirconia ceramic material for dental restoration is obtained, wherein the process conditions for the high-temperature sintering are: heating to 550°C at a rate of 1°C / min, keeping warm for 3 hours, then heating to 950°C at a rate of 2°C / min and keeping warm for 2 hours, then heating to 1430°C at a rate of 3°C / min and keeping warm for 1 hour, then cooling to 500°C at a rate of 2°C / min, keeping warm for 5 hours for tempering, and finally cooling to room temperature at a rate of 20°C / min.
[0035] Comparative Example 1 The same as Example 3, except that the composite spherical powder is the composite spherical powder prepared in Comparative Example 1.
[0036] Comparative Example 2 The same as Example 3, except that, S1, preparing the green body: the composite spherical powder (the composite spherical powder prepared in Preparation Example 2) is compression molded at a pressure of 10 MPa to obtain a molded green body with a volume of V, and the green body is vacuum packed; the packaged green body is placed in a 130°C hot isostatic press, pressurized to 190 MPa, maintained at pressure for 20 minutes and then released to obtain a hot-pressed green body with a volume of 87% V.
[0037] Comparative Example 3 The same as Example 3, except that, S1, preparing the green body: the composite spherical powder (the composite spherical powder prepared in Preparation Example 2) is compression molded at a pressure of 10 MPa to obtain a molded green body with a volume of V, and the green body is vacuum packed; the packaged green body is placed in a 170°C hot isostatic press, pressurized to 220 MPa, maintained at pressure for 20 minutes and then released to obtain a hot-pressed green body with a volume of 80% V.
[0038] Comparative Example 4 The same as Example 3, except that, S2, high temperature sintering: after the hot pressed green body is unpacked, it is sintered at high temperature to obtain a nano zirconia ceramic material for dental restoration, wherein the process conditions of the high temperature sintering are: heating to 550°C at a rate of 1°C / min, keeping warm for 3h, then heating to 950°C at a rate of 2°C / min and keeping warm for 2h, then heating to 1430°C at a rate of 3°C / min and keeping warm for 1h, and then naturally cooling to room temperature with the furnace.
[0039] Performance Testing The nano-zirconia ceramic materials for dental restoration prepared in Example 1, Example 3 and Comparative Examples 1 to 4 were sampled and tested as follows. The test results are shown in Table 1.
[0040] The four-point bending strength test is carried out in accordance with GB / T 6569-2006 "Fine Ceramics Bending Strength Test Method" standard; the fracture toughness test is carried out in accordance with GB / T 23806-2009 "Fine Ceramics Fracture Toughness Test Method - Single-Sided Pre-Crack Method" standard; antibacterial performance: antibacterial testing is carried out in accordance with JIS Z2801:2000 standard, the antibacterial rate of Staphylococcus aureus ATTCC6538P and Escherichia coli ATCC8739.
[0041] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The nano-zirconia ceramic materials for dental restoration prepared in Examples 1 to 3 have excellent mechanical properties (high bending strength, high fracture toughness), biocompatibility, chemical stability and antibacterial properties. At the same time, the preparation method of the present invention has simple process and low cost, and can be effectively applied to mass production. In addition, the nano-zirconia powder prepared in the present application has a large specific surface area, a small particle size and a uniform particle size distribution, stable tetragonal phase crystals and excellent antibacterial properties.
[0042] 2) The performance comparison analysis of the nano zirconium oxide ceramic material for dental restoration prepared in combination with Example 3 and Comparative Example 1 shows that the nano zirconium oxide powder prepared in this application is modified by embedding soluble zirconium salt and yttrium salt with carboxymethyl cellulose, and the synergistic effect of surfactant and glycerol makes zirconium salt, yttrium salt and silver salt uniformly dispersed during the precipitation process, and the final zirconium oxide particles are smaller in size and evenly distributed. This modification method not only improves the strength and toughness of the material, but also enhances its antibacterial properties and biocompatibility. Compared with yttrium-stabilized zirconium oxide on the market, it has better performance and antibacterial properties.
[0043] 3) The comparative analysis of the performance of the nano-zirconia ceramic material for dental restoration obtained in combination with Example 3 and Comparative Examples 2-3 shows that in the process of preparing the green body, by precisely controlling the process conditions of hot pressing and static pressing, a hot-pressed green body with a volume of 83%V is obtained, which is better than other hot-pressed green bodies such as 80%V or 87%V hot-pressed green bodies, and the performance of the nano-zirconia ceramic material finally obtained is better.
[0044] 4) The performance comparison analysis of the nano-zirconia ceramic material for dental restoration prepared in combination with Example 3 and Comparative Example 4 shows that the present invention can further improve the mechanical properties of the nano-zirconia ceramic material by cooling to 500°C at a rate of 2°C / min, keeping it warm for 5 hours, and finally cooling to room temperature at a rate of 20°C / min and keeping it warm for tempering. At the same time, it can also avoid processing defects such as chipping, cracks and holes, improve the density and uniformity of the material, and then improve the balance between the strength and toughness of the nano-zirconia ceramic material, and extend the service life of the nano-zirconia ceramic material.
[0045] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a nano-zirconia ceramic material for dental restoration, characterized in that: The following steps are involved: S1, preparing nano zirconium oxide powder; S2. Preparation of composite spherical powder: The composite spherical powder includes the following raw materials by mass: 100 parts of nano zirconium oxide powder, 3 parts of barium glass powder, 3.5 parts of binder, 1 part of dispersant, 10 parts of ethanol, and 140 parts of deionized water; S3, preparing a green body: molding the composite spherical powder under a pressure of 10 MPa to obtain a molded green body with a volume of V, and vacuum packaging the green body; placing the packaged green body into a 170° C. hot isostatic press, pressurizing it to 200 MPa, maintaining the pressure for 20 minutes, and then releasing the pressure to obtain a hot pressed green body with a volume of 83%V; S4. High temperature sintering: After the hot pressed green body is unpacked and subjected to high temperature sintering, the nano-zirconia ceramic material for dental restoration is obtained.
2. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 1, characterized in that: In step S1, the method for preparing nano zirconium oxide powder comprises the following steps: S21, adding a soluble zirconium salt, a soluble yttrium salt, silver nitrate, a surfactant, glycerol, and carboxymethyl cellulose into deionized water, and dissolving them to form a solution A; S22, adding solution A dropwise to an alkaline precipitant to carry out precipitation reaction for 40 minutes, then adding oleic acid and stirring for reaction for 30 minutes to obtain a suspension; S23, aging the suspension at 35° C. for 24 hours, filtering, washing with water and washing with alcohol to obtain a hydrated zirconium gel; S24. The hydrated zirconium gel was heated for 20 minutes under a microwave condition with a power of 500 W for drying, and then calcined at 480° C. in an air atmosphere for 2.5 hours to obtain nano zirconium oxide powder.
3. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 2, characterized in that: In step S21, the soluble zirconium salt is zirconium oxychloride octahydrate; the soluble yttrium salt is yttrium acetate; and the surfactant is composed of coconut oil fatty acid diethanolamine and lauryl alcohol polyoxyethylene ether in a mass ratio of 1:
2.
4. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 2, characterized in that: In step S21, the mass ratio of the soluble zirconium salt, the soluble yttrium salt, silver nitrate, the surfactant, glycerol, carboxymethyl cellulose and deionized water is 322:45:9:65:20:13:
500.
5. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 2, characterized in that: In step S22, the alkaline precipitant is prepared by mixing ammonium carbonate and 25% ammonia water in a mass ratio of 5:
7.
6. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 2, characterized in that: In step S22, the mass ratio of oleic acid to solution A is 1:80-90.
7. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 2, characterized in that: In step S2, the binder is composed of polyvinyl alcohol and hydroxy cellulose in a mass ratio of 1:1; and the dispersant is ammonium citrate.
8. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 1, characterized in that: In step S2, the preparation method of the composite spherical powder is as follows: according to the mass fraction, nano zirconium oxide powder and barium glass powder are placed in a polyurethane-lined ball mill, and zirconium oxide beads 3 times the mass of the nano zirconium oxide powder are added at the same time, and then deionized water, ethanol and dispersant are added in sequence, at a speed of 50 rpm; after ball milling for 0.6 h, a binder is added and ball milling is continued for 1.2 h; the slurry is filtered to obtain a slurry, and the slurry is sprayed and granulated. During granulation, the feed inlet temperature is 260°C, the discharge port temperature is 115°C, the atomization frequency is 170 Hz, and the blowing pressure is 0.6 MPa to obtain a composite spherical powder.
9. The method for preparing a nano-zirconia ceramic material for dental restoration according to claim 1, characterized in that: In step S4, the process conditions of high-temperature sintering are as follows: heating to 550°C at a rate of 1°C / min, keeping warm for 3 hours, then heating to 900-1000°C at a rate of 2°C / min and keeping warm for 2 hours, then heating to 1400-1450°C at a rate of 3°C / min and keeping warm for 1 hour, then cooling to 500°C at a rate of 2°C / min, keeping warm for 5 hours for tempering, and finally cooling to room temperature at a rate of 20°C / min.
10. A nano-zirconia ceramic material for dental restoration, characterized in that: The nano-zirconia ceramic material is prepared by the method for preparing the nano-zirconia ceramic material for dental restoration according to any one of claims 1 to 9.
Citation Information
Cited By
Dental repair composite material suitable for DLP 3D printing technology and preparation method thereof
CN121015460A